NYÈSÈK 'S CULTURAL TRANSFORMATION IN THE SASAK TRIBE COMMUNITY IN SADE TOURISM VILLAGE, CENTRAL LOMBOK - Setianny, Evit Nurul (E-Journal of Cultural Studies; Vol 17 No 3 (2024): Volume 17 Number 3 August 2024, 2024)
Sade is a hamlet inhabited by the Sade indigenous peoples in Central Lombok. The culture of the ancient Sasak tribe is still implemented by the Sade people to this day. One of them is the Nyèsèk tradition. Nyèsèk is a tradition of weaving cloth which is also a symbol of maturity and a condition for marriage for women of the Sasak Sade tribe. This tradition was originally private because it was only inherited to girls, but as the times rolled in, the tradition of weaving this cloth then underwent a transformation from being private to a side job for housewives in Sade hamlet. The determination of Sade hamlet as a Tourism Village in 1989 made this tradition undergo a second transformation where the Nyèsèk tradition is a commercialized cultural attraction. Based on the background of the problems presented, the purpose of this study is first, to analyze the factors that cause the Nyèsèk tradition to undergo cultural transformation. Second, to analyze the forms of cultural transformation in the Nyèsèk tradition. Third, to understand the implications of cultural transformation in the Nyèsèk tradition in Sade Tourism Village. This study uses qualitative research methods and data collection techniques through observation, interviews and document studies. The theories used in this study are social practice theory and social-being theory. The data analysis in this study uses inductive analysis. The results of the study show that first, the cause of the Nyèsèk tradition undergoing cultural transformation is divided into two, namely internal factors originating from the Sade community in the form of economic factors and external factors originating from the needs of tourists, namely the trend of cultural tourism which is strengthened by the role of the government in developing cultural tourism on the island of Lombok. Second, the form of cultural transformation of Nyèsèk is a transition from being private, then to domestic sector work and finally to the public sector. Third, the implications of the transformation of the Nyèsèk culture are divided into two, namely positive implications which affect the improvement of people's welfare and negative implications that obscure the essence of the tradition of the ancestral heritage of the Sasak tribe. Keywords : cultural transformation, nyèsèk , sade, sasak tribe